Establishment of an Interprofessional, Student-Led, Community-Based, Free Clinic - White, Lanita; Franks, Amy; Ragland, Denise (Journal of Student-Run Clinics, 2018)
This report describes an innovative, team-based model for the development of an interprofessional, student-led, community-based, free clinic. The 12th Street Health and Wellness Center’s creation was a direct collaboration of university administration, faculty from the various university colleges, students, and the community for the purpose of providing basic healthcare for the neighboring medically underserved population. Inclusion of the target community in the planning and implementation processes allowed for easy identification of neighborhood needs while providing community stakeholders a leadership role in creation and operations. Challenges in establishing the clinic are discussed including financial support, volunteer recruitment, and scheduling. Primary care services are provided by student teams from five colleges and a graduate school in a model that engages all students in interprofessional interactions throughout the patient visit. Each student team presents their assessment and plan to an interprofessional preceptor team who oversees and facilitates discussions regarding refining the diagnosis, identifying further assessment needed, and outlining the most appropriate plan. This model of patient care is embraced by students, preceptors, and patients while providing the opportunity for interprofessional education as healthcare students from several professions learn from, about, and with each other.